Educação superior e acesso : estudo sobre a Universidade Federal de Mato Grosso no contexto contemporâneo de expansão - Pinto, Ana Paula (2014)
The purpose of this paper is to present a theoretical and political reflection on the politics of access to higher education in the national context in which education is elencada as an economic good and a strategy to reduce poverty and unemployment, reducing inequalities. The reform of the state apparatus from the 1990s impact on redefining the role of higher education. In this sense, it approaches the effects of this new rationality of the State linked to 'new' logic of finance capital in higher education, it is rejuvenated the Theory of Human Capital highlighting education as an almost magical solution to the problems of inequality . Paradoxically, this direction are born educational policies of expansion of higher education, while the struggle for democratization is present in the correct historical perspective of elitism in higher education in Brazil. Taking as reference a reading of the historical, socio-political and economic contemporary and seeks to analyze the study and discuss the process of democratization of Brazilian education, which did expand predominantly in the enrollment of students in universities, with protagonist presence determinations of the private over the public. In this scenario and context PROUNI, REUNI and Enem mechanisms boosters are putting up a challenge to analysis of this process in Mato Grosso, particularly on the Federal University of Mato Grosso in order to understand how to configure the access policy in UFMT, and finally indicates how these current policies have been developed to meet the demand of young students, the working class historically excluded from this level of education. As a concluding summary, significant data entry, enrollment, residence, among others, show progress, but still far from gaining education as a universal right, which confirms how education, when apprehended in terms of social relations and determinations and therefore, itself constituted and constituent of these relationships, presents history as a field of hegemonic dispute.